If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 6 = -2 + -3 Reorder the terms: 6 + x = -2 + -3 Combine like terms: -2 + -3 = -5 6 + x = -5 Solving 6 + x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = -5 + -6 Combine like terms: 6 + -6 = 0 0 + x = -5 + -6 x = -5 + -6 Combine like terms: -5 + -6 = -11 x = -11 Simplifying x = -11
| Tan2x=3/2secx | | 400a+4=18*365a+7 | | 6=-x+293 | | Tan^2x=3/2secx | | -8v+12=-4(v-9) | | 2x=10(15-3x) | | 3(1)-2y=-6 | | 2(1-e)=3e-8 | | -5(u-3)=-2u-3 | | 2.5*ln(x)-ln(2x)=0 | | 7n+5n=-12 | | 3/8w=5 | | 5w+4-9w-3= | | -6x=3y-1 | | 4x^6+9x^2-2=0 | | Cosx+senx=0 | | w=8+2.5T | | 3w+2=5(w+2) | | X/9=-52 | | (9x)/(7-6x)=15 | | -5(w-6)=-2w+24 | | 5+3*5-1=19 | | 5*x1/2=4 | | 511/2-223 | | 12-4m=6-3m | | 14/5=2x | | 8(0)+2y=-4 | | 4x=6(4.8) | | 11a+9b-2c= | | 8(1)+2y=-4 | | 9•1/3= | | 4y+25=-7(y+9) |